Prenatal Cocaine Exposure and Infantile Psychomotor Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The effects of prenatal cocaine exposure on child development outcomes were studied prospectively in an obstetric unit of a large US urban teaching hospital at Case Western Reserve University, Cleveland, OH.